IMPLEMENTASI MODEL PROBLEM BASED LEARNING (PBL) PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Afrilianto, Deris (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2024)
The background of the writing began in the VIII grade PAI learning activities at SMP N 1 Jujuhan Ilir, Bungo Regency, Jambi Province. In practice, it is still found that students only accept what the teacher says but do not really understand it. This is caused by teaching and learning activities that are still less effective carried out by teachers. Teachers do not associate problems in the surrounding environment with learning at school. The purpose of the study was to determine the learning process of Problem Based Learning (PBL), the impact of implementation in the learning process of Islamic Religious Education in Class VIII SMP N 1 Jujuhan Ilir, Kab. Bungo, Jambi. The type of research used is descriptive qualitative research. This type of research is a qualitative descriptive research. The informants of this research are PAI teachers as key informants and supporting informants, namely teachers and students of class VIII. Data collection techniques are interviews, observations, and documentation. Data analysis techniques are data reduction, data presentation, and data collection. Then the author's data validity technique uses data triangulation and source triangulation. The results showed that the learning process of Islamic Religious Education in Class VIII SMP N 1 Jujuhan Ilir, Kab. Bungo, Jambi has implemented the Problem Based Learning (PBL) Model which has an impact on increasing students' critical thinking, making Islamic Religious Education learning more contextual, fun, and directed.